Role of hyaluronic acid in the prevention and treatment of radiation-induced oropharyngeal mucositis - Yu. V. Alymov; А. М. Mudunov; S. B. Alieva; А. V. Ignatova; R. R. Kaledin; А. М. Avanesov (Опухоли головы и шеи)
One of the earliest and most common adverse events of radiotherapy in patients with oropharyngeal cancers is mucositis. Radiation-induced mucositis significantly impairs the quality of life, patient compliance, and sometimes even long-term treatment outcomes. Currently, there is a wide range of drugs and techniques for the prevention and treatment of this complication. Nevertheless, these methods are not always highly effective and often have their own adverse events; therefore, the search for a universal method still continues. The present review aims to analyze the efficacy of hyaluronic acid in the prevention and treatment of oropharyngeal mucositis.